Leveraging Partnerships for Microcredential Design in Digital Health: Key success factors - Sheree Lloyd; Mark Upton; Joel Scanlan (Asia Pacific Journal of Health Management)
Aim: This paper describes the collaborative approaches used to design microcredentials in digital health and cybersecurity. The project was initiated to design and deliver educational products to address specific skills shortages and align outcomes with Australian and International skills and professional competency frameworks.